IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 73 TAHUN 2018 TENTANG SISTEM TEKNOLOGI INFORMASI SMART RESCUE DALAM PELAYANAN PEMADAMAN KEBAKARAN - winda safira (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2022)
This study aims to find out the implementation of Pekanbaru Mayor Regulation Number 73 of 2018 concerning Smart RescueInformation Technology Systems in FireFighting Services and find out what factors affect the implementation of Pekanbaru Mayor Regulation Number 73 of 2018 concerning Smart RescueInformation Technology Systems in FireFighting Services. The approach used in this study is a qualitative approach and this research uses a descriptive type of research. The informants in this study were the IT of the Pekanbaru Fire Service, the Secretary of Fire And Investigation, the General Kasubag Staff, the Logistics Distribution Kasi, and the Community. Data analysis is carried out in a descriptive way. The results showed that the implementation of Pekanbaru Mayor Regulation Number 73 of 2018 concerning Smart RescueInformation Technology Systems in Fire Fighting Services consisted of three aspects as follows: The program, based on research conducted, the issuance of Pekanbaru Mayor Regulation Number 73 of 2018 was used as a foundation by the fire department as a backdrop in carrying out service innovations. Program Implementer, the study found The weak responsiveness of the fire department in responding to community complaints through the Smart Rescue application caused the fire department to not be able to increase the percentage of Smart Rescueusers in Pekanbaru. The target group, based on the research conducted, found that stakeholders have not been optimal in socializing the use of the Smart Rescueapplication to all Stakeholders and the community in Fire Services, this is characterized by the small number of Smart Rescueapplication users. Factors Causing the Failure to Implement Pekanbaru Mayor Regulation Number 73 of 2018 concerning Smart RescueInformation Technology Systems in Fire Fighting Services are: The absence of communication between stakeholders and the community and suboptimal resource performance.